Designing of Combinational Fractal Microstrip Patch Antenna using Iteration Methods (International Journal of Engineering and Computer Science, 2014)
This paper presents a design of microstrip patch antenna combining Crown and Sierpienksi fractal slots by cutting different slots on rectangular microstrip antenna and experimentally studied on IE3D software. This design is achieved by cutting multi shapes in square pattern combining with Crown & Sierpienksi fractal slots & placing a microstrip line feed. This design has been studied in 3 iterations. The radiation pattern of the proposed fractal shaped antennas maintained because of the self similarity and centro-symmetry of the fractal shapes. With fractal shapes patch antenna is designed on a FR4 substrate of thickness 1.524mm and relative permittivity of 4.4 and mounted above the ground plane at a height of 6 mm. Details of the measured and simulated results of the individual iterations are presented & discussed.